Financial Access (FACS) and The Alliance of Bioversity International – CIAT are working together to advance financial inclusion for smallholder farmers in Africa - Financial Access (FACS); Bioversity International and International Center for Tropical Agriculture (2023)
Inclusion for smallholder farmers is a key element in inclusive growth. It allows for them to make longer-term investments, consumption decisions, participate in productive activities, and adapt to unexpected climate shocks through the role which financial instruments can play in risk reduction and transfer.